THE 9TH INTERNATIONAL WORKSHOP "PHYSICS AND FORECASTING OF ROCK DESTRUCTION" - V. V. Ruzhich; A. D. Zavyalov; A. A. Dobrynina; S. A. Bornyakov (Геодинамика и тектонофизика)
The 9th International Workshop “Physics and Forecasting of Rock Destruction” was held in the Institute of the Earth’s Crust, SB RAS, in Irkutsk on 02–06 September 2013. The article reviews the main events of this scientific forum and briefly describes its discussion results concerning prediction / forecasting of dynamic destruction of rocks due to loading in various regimes and scales. Also reviewed are options for improvement of forecast methods and their application to practice.